2014
DOI: 10.1002/eco.1559
|View full text |Cite
|
Sign up to set email alerts
|

Comparing two approaches for parsimonious vegetation modelling in semiarid regions using satellite data

Abstract: Large portions of Earth's terrestrial surface are arid or semiarid. As in these regions the hydrological cycle and the vegetation dynamics are tightly interconnected, a coupled modelling of these two systems is needed to fully reproduce the ecosystem behaviour and to predict possible responses to climate change. In this paper, the performance of two parsimonious dynamic EVI is reported in literature to be highly correlated with leaf area index so it is compared with modelled LAI mod (r WUE-model =0.45; r LUE-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 80 publications
0
41
0
5
Order By: Relevance
“…Evidence of aET being a prevalent driver of hydrological records of streamflow and water table depth, i.e., available water resources, has been observed in many studies (Bond et al, 2002;Nyholm et al, 2003;Gribovszki et al, 2008;Conradt et al, 2013). Recently, Tsang et al (2014) showed that adding a better evapotranspiration scheme in a widely used runoff model improves streamflow predictions.…”
Section: G Ruiz-pérez Et Al: Calibration Of a Parsimonious Distribumentioning
confidence: 98%
See 4 more Smart Citations
“…Evidence of aET being a prevalent driver of hydrological records of streamflow and water table depth, i.e., available water resources, has been observed in many studies (Bond et al, 2002;Nyholm et al, 2003;Gribovszki et al, 2008;Conradt et al, 2013). Recently, Tsang et al (2014) showed that adding a better evapotranspiration scheme in a widely used runoff model improves streamflow predictions.…”
Section: G Ruiz-pérez Et Al: Calibration Of a Parsimonious Distribumentioning
confidence: 98%
“…On the plot scale, Quevedo and Francés (2008) and Pasquato et al (2015) calibrated and validated a parsimonious ecohydrological model using satellite information. More recently, Ruiz-Pérez et al (2016) discussed the applicability of satellite data during the calibration process comparing the results obtained by a parsimonious model calibrated using only satellite data against the results obtained by a complex model calibrated using field measurements on the pixel scale.…”
Section: Satellite Data and Model Calibration And Validationmentioning
confidence: 99%
See 3 more Smart Citations